Pengembangan Media Interaktif Berbasis Canva untuk Meningkatkan Minat Belajar Murid TK Go Ceria Cipayung - Ryantina, Dessyanti; Pasaribu, Wealty Sweet Charollyn; Widiyanti, Eva (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Interactive is a media that provides an opportunity for users to interact with the media and practice skills and get feedback on the material displayed. This study aims to determine the development of interactive media based on the Canva application to increase the learning interest of students at Go Ceria Cipayung Kindergarten. Kindergartens play an essential role in forming the foundation for the development of children's knowledge, attitudes, and skills. The main priorities of early childhood education include stimulation, guidance, care, and learning activities. Learning media, especially interactive educational media, are important to motivate and understand children. This study focuses on the development of multimedia-based interactive media using Canva for Go Ceria Cipayung Kindergarten. The objectives of this study include the creation of interactive media, as a reference for learning activities while playing, and measuring its effectiveness in TK Go Ceria Cipayung. The conclusion of this study shows that interactive learning media using cnva has been successfully designed, has the potential to foster a sense of interest in learning in the younger generation, especially students of TK Go Ceria Cipayung.